RISK ANALYSIS OF HEAVY METAL (PB) EXPOSURE THROUGH DERMAL ROUTE ON DNA DAMAGE IN WORKERS IN SOME PAINT INDUSTRY IN INDONESIA - Nur'azizah Rahman, Intan
Lead (Pb) as a toxic heavy metal is still used in paint production process in Indonesia as a pigment, dryer or anti-corrosion agent and some paint industries still exceed the standard for Pb content in paints set out in SNI 8011-2014. It has the potential to be a major source of lead exposure to paint industry workers via the dermal route during the paint production process. Blood lead levels (PbB) are often used as biomarkers of lead exposure. Lead as an exogenous factor can cause oxidative stress due to accumulation of Reactive Oxygen Species (ROS) and can inhibit antioxidant defense enzymes. Imbalance of Reactive Oxygen Species (ROS) and antioxidant defenses can cause DNA damage which can be used as a biomarker of the effects of lead. So it is necessary to investigate the genotoxic effects of lead on paint industry workers in Indonesia. The aims of this study was to analyse the health risks of paint industry workers of Pb exposure via dermal routes, determine the relationship between Pb exposure and PbB levels, and determine the relationship between PbB levels and DNA damage using a crosssectional epidemiological study of 52 workers from three paint industries in Indonesia. Samples of Pb exposure via the dermal route were measured based on NIOSH 7702 issue 1 using a 0.8 µm pore MCE patch filter, Ø=47 mm attached to exposed body parts for 3 hours, while the Pb content in the air was measured using LVAS (PTFE filter; 45 µm; Ø=47 mm; flow rate 2.5 LPM) based on SNI 16-7058-2004 as many as 5 sampling points in each industry. However, the limitations of this study were that each point was measured for 3 hours, which was then analysed using EDXRF. As many as 6 mL of blood samples were taken to determine PbB levels which were analyzed using ICP-MS and 3 mL to analyse DNA damage using the Comet Assay method. Interviews were conducted to determine the characteristics of the respondents. The Pb content in occupational environment (indoor) is 0.113 ± 0.165 µg/m3 , and below the standards set by Permenaker RI 5/2018. However, the dose received by workers through the dermal route is 3.69x10-6 ± 8.13x10-6 mg/kg.day and resulting a non-carcinogenic risk (HQ>1) from 1 worker in industry C, so it is necessary to carry out risk management, such as elimination, substitution, engineering control or use of PPE. Meanwhile, the carcinogenic risk (ELCR) was still within acceptable limits, 4.95x10-8±1.21x10-7 mg/kg.day. The PbB level was 4.22 ± 1.6 µg/dL, and 17 workers exceeded the safe limit (5 µg/dL), as many as 1 worker from industry A and B, respectively. While, 15 workers (88.24%) were obtained from industry C. Pb exposure via the dermal route was significantly positively correlated with PbB levels (p=0.04; r=0.39). Factors affecting PbB levels were length of work and alcohol consumption (p<0.05). Meanwhile, PbB levels were negatively correlated with Tail DNA (%) (r=-0.049) and Tail Length (µm) (r=-0.047), and positively correlated with Tail moment (µm) (r=0.159), but not significant (p >0.05). The value of Tail DNA (%) for workers was 9.62 ± 0.19%, all workers were classified as having low DNA damage (Class 2). Pb exposure in this study has not reached a level that can significantly cause DNA damage. However, it is necessary to monitor blood lead levels in workers due to indications of an increase in the Tail Moment (µm) due to dermal Pb exposure.